Relationship between the position of maxilla and rapid maxillary expansion failure - Celebi, Fatih (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Introduction: The palatal expansion may be a challenging treatment in late adolescents who has passed the peak of skeletal growth. The success rate of palatal expansion in these patients decreases due to decreased growth potential. Aim: It was aimed to determine any clinical/radiological indicator to be used as a predictor in the failure of rapid maxillary expansion (RME) in late adolescence. Materials and methods: The records of the patients who had undergone RME therapy between the years 2013-2019 were evaluated. The patients were allocated into two groups according to expansion success: successful (S-RME) and failed (F-RME) RME groups. Fifty systemically healthy patients in the cervical vertebral maturation stage 5/6 were enrolled (35 females, 15 males). Eleven patients were (10 females, one male) in the F-RME group, and 39 patients were (25 females, 14 males) in the S-RME group. Five cephalometric (related to maxillary position) and three clinical variables (age, gender, and CVMS) were evaluated. Variables were subjected to multiple logistic regression analysis for setting a prediction model and detecting predictors. Results: Patients with CVMS-6 had a 16.8-fold higher risk of palatal expansion failure than CVMS-5. 1 mm anterior position of PNS increased the risk of failure 2.9 times. 1 mm reduction in the distance between the PNS and cranial base in the vertical direction increased 60% the risk of RME failure. Conclusion: The CVM stage of the patient, along with the vertical and sagittal position of the PNS, were found to be the possible predictors of RME success in late adolescence.